Jewish and Roman Catholic Approaches to Access to Health Care and Rationing - Mackler, Aaron L (Kennedy Institute of Ethics journal, 2001)
, In addressing issues of access to health care and rationing, Jewish and Roman Catholic writers identify similar guiding values and specific concerns. Moral thinkers in each tradition tend to support the guarantee of universal access to at least a basic level of health care for all members of society, based on such values as human dignity, justice, and healing. Catholic writers are more likely to frame their arguments in terms of the common good and to be more accepting of rationing that denies beneficial and needed health care to some persons. Jewish writers are more likely to consider individual responsibility for illness in allocation decisions and to accept differences in the health care that different members of society receive. The article considers the relevance of both shared and complementary perspectives for deliberations in nations such as the United States.